Pengaruh Variasi Ukuran Media Arang Aktif Cangkang Kelapa Sawit terhadap Penurunan Kadar Besi dan Kekeruhan pada Air Sumur - Sani, Fajar Mavira; Haryono, Haryono; Rois, Ibnu; Mulyaningsih, Tri (Poltekkes Kemenkes Bengkulu, 2025)
Water is a fundamental necessity for human life and is required to comply with both quality and quantity standards. Excessive iron (Fe) content and turbidity can negatively impact life. An alternative effort to reduce Fe and turbidity levels exceeding quality standards is filtration using palm shell activated carbon. This study aims to investigate the effect of varying particle sizes of activated carbon made from oil palm shell on the reduction of iron (Fe) content and turbidity in well water. This study employed a quasi-experimental design with a Pre-Test – Post-Test Without Control Group. The research object was well, located in Ngumbul, Tamanan, Bantul. Three variations of palm shell activated carbon media were used: Filter A: 1 cm, Filter B: 0.5 cm, Filter C: 0.2 cm, each with three repetitions per variation, which was then followed by inferential analysis. Descriptive analysis showed reductions in Fe and turbidity as follows: Filter A – Fe 1.22 mg/L and turbidity 43.97 NTU, Filter B – Fe 1.15 mg/L and turbidity 38.22 NTU, Filter C – Fe 1.27 mg/L and turbidity 43.97 NTU. The result of the One-Way ANOVA test showed that there was no significant effect of the variation in the particle size of activated carbon made from oil palm shell on the reduction of iron content and turbidity. Palm shell activated carbon is effective in reducing iron (Fe) content and turbidity in well water.